Analisis Resepsi Sastra dalam Cerpen Perhiasan Bumi Karya Korrie Layun Rampan - Rindaningtyas, Yulita Dwi; Arifin, Syaiful; Putri, Nina Queena Hadi (Adjektiva: Educational Languages and Literature Studies, 2019)
This study aims to determine the reception of readers, namely students of Indonesian Language and Literature Education Class of 2017, Mulawarman University, on the intrinsic elements in Korrie Layun Rampan's short story Perhiasan Bumi and its implications for literary learning in the Indonesian Language and Literature Education Study Program based on Rachmat Djoko Pradopo's reception theory. The research method used is descriptive qualitative research methods. The data collection techniques used were reading techniques and note taking techniques obtained from research questionnaires, namely questionnaires. The data used in this research is the reader's reception of Korrie Layun Rampan's Perhiasan Bumi short story. The results of this study are in the form of a reader's reception for the short story “Perhiasan Bumi” by Korrie Layun Rampan and its implications for literature learning in the Indonesian Language and Literature Education Study Program. Based on the data analysis, the results obtained include the reader's reception of the intrinsic elements of the short story of the Perhiasan Bumi by Korrie Layun Rampan which was produced after the respondent answered seventeen questions on the questionnaire, and three answers were found that are the same from the respondent on the implications of the reader's reception on the short story in literature learning.